Relational social work : toward networking and societal practices - Folgheraiter, Fabio (Jessica Kingsley Publishers, 2004)
In making a contribution to the international social work literature this book reaffirms the importance to social work theory and practice of recognising, across our differences, common concerns with social change, social ideas and social movements.' - from the Foreword by Professor Ann Davis In this innovative book, a revised English edition of an important Italian text, Fabio Folgheraiter presents a systematic introduction to networking and reflexive practice in social work. He draws on Italian experience and practice in community care and development to foster a deeper understanding of the relational core of social 'problems' and 'solutions', demonstrating an alternative approach to the current trend in positivistic evidence-based methods. The text explores how the interested parties in social care (users, carers, neighbours, volunteers, professional workers, managers, policy makers) can acquire a shared power in care planning and decision making. Folgheraiter demonstrates that when this networking and empowerment occurs, caring initiatives become truly social based and their efficacy increases. This book provides the framework for the repositioning of social care practice in relation to the state and civil society. The model of practice proposed is an important step towards the development of networks that can effect change locally, nationally and globally.